Structural Transformation, Productivity, and Employment in Ghana 1991-2012 - Paci, Pierella; Pavelesku, Dan (World Bank, Washington, DC, 2015)
Ghana’s recent economic growth was accompanied by significant structural transformation. Over the past two decades Ghana has enjoyed sustained economic growth combined with some degree of transformation away from agriculture. This shift was associated with a considerable increase in the relative share of services. In recent years, the industry share of GDP has also picked up although the growth of employment in that sector has been comparatively slow.